Comparison of the Short-Term and Long-Term Effects of Surgery and Nonsurgical Intervention in Treating Carpal Tunnel Syndrome: A Systematic Review and Meta-Analysis. (January 2020) - Shi, Qiyun; Bobos, Pavlos; Lalone, Emily A.; Warren, Laura; MacDermid, Joy C.
Background: The objective of the study is to examine the short-term and long-term efficacy of surgical treatment of carpal tunnel syndrome (CTS) compared with conservative treatment (ie, splint, steroid injection, or physical therapy).Methods: Two reviewers searched the Cochrane Central Register of Controlled Trials, MEDLINE, EMBASE, and PEDro up to September 2017. Quality appraisal and data extraction were performed in duplicate. Patient self-reported functional and symptom changes, as well as improvement of electrophysiological studies, were assessed as outcomes. Meta-analyses were performed in RevMan.Results : From 1438 studies identified after searching, 10 remained for analysis after exclusion criteria were applied. Moderate-quality evidence indicated that surgical interventions were superior to splint or steroid injection at 6 months with a weighted mean difference of 0.25 (95% confidence interval [CI], 0.07-0.44) for functional status and 0.64 (95% CI, 0.07-1.21) for symptom severity. The surgical group had better nerve conduction outcomes at 6 months (0.57 [95% CI, 0.05-0.50] ms). No significant differences were observed at 3 or 12 months.Conclusions: Both surgical and conservative interventions provide treatment benefits in CTS. Further studies on long-term outcome are needed.